2016
DOI: 10.4067/s0718-93032016000200004
|View full text |Cite
|
Sign up to set email alerts
|

La selección modal del subjuntivo/indicativo en el Corpus sociolingüístico Preseea-Medellín

Abstract: Este artículo es un resumen de una tesis de maestría del mismo título. Agradezco a la Dra. Marianne Dieck por su cuidadosa dirección y revisión de la tesis. Sin embargo, asumo la responsabilidad de cualquier error de contenido o de redacción.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…With respect to L1, it has been found that, even though children acquire Spanish subjunctive morphology early in the language acquisition process, they only master mood selection in relative clauses around the age of 12 (Blake 1983), showing a correlation between cognitive and linguistic development (Pérez-Leroux 1998). This contrast is also lost early in attrition (Lipski 1993;Lynch 1999;Merino 1983;Silva-Corvalán 1994Zentella 1997) and is subject to variation among native speakers (Blake 1983;Koenig 2016;Murillo 2000). Previous studies comparing L2 and HL speakers, have found that HL speakers, who acquire the language from birth, are not necessarily more native-like than L2 learners when it comes to structures that are acquired late, as is the case with mood selection in Spanish relative clauses (Montrul and Perpiñán 2011).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to L1, it has been found that, even though children acquire Spanish subjunctive morphology early in the language acquisition process, they only master mood selection in relative clauses around the age of 12 (Blake 1983), showing a correlation between cognitive and linguistic development (Pérez-Leroux 1998). This contrast is also lost early in attrition (Lipski 1993;Lynch 1999;Merino 1983;Silva-Corvalán 1994Zentella 1997) and is subject to variation among native speakers (Blake 1983;Koenig 2016;Murillo 2000). Previous studies comparing L2 and HL speakers, have found that HL speakers, who acquire the language from birth, are not necessarily more native-like than L2 learners when it comes to structures that are acquired late, as is the case with mood selection in Spanish relative clauses (Montrul and Perpiñán 2011).…”
Section: Introductionmentioning
confidence: 99%